A Matter of Time: Delayed Presentation and Rapid Progression from Gonadotropin-Independent to Gonadotropin-Dependent Precocious Puberty following Successful Treatment for a Leydig Cell Tumor - C. R. Naotunna; D. N. Siriwardana; B. C. Lakmini; M. Samarasinghe; N. Atapattu (Hindawi Limited, 2022)
Leydig cell tumors, most often benign, are a rare cause of isosexual gonadotropin-independent precocious puberty in boys due to secretion of testosterone. Very rarely do these tumors produce estrogen, causing gynecomastia. Testicular sparing surgery is the mainstay of treatment currently although radical orchidectomy was the choice in the past. Following surgery, clinical signs improve along with a revision of biochemical changes. Occasionally, it has been reported few children are progressed to gonadotropin-dependent precocious puberty (GDPP) after initial clinical and biochemical recovery. Gonadotropin receptor analogs have been successful on them to halt the progression of puberty, and growth hormone administration has been used to optimize the adult height. Here, we report a case of a 10-year-old boy who presented very late due to failure in recognition of features of puberty due to a Leydig cell tumor. Even though he underwent successful radical orchidectomy, just within 1 month following surgery, he entered GDPP in contrast to the published cases where it was earliest detected at 3 months.